Approaches Employed By Secondary School Teachers To Teaching The Literature Component In English - Diana Hwang, Diana Hwang; Embi, Mohamed Amin (Penerbit Universiti Sains Malaysia, 2007)
The purpose of this article is to report on findings of a study designed to identify approaches employed by teachers to teaching the literature component in selected secondary schools in Sabah. The study was conducted in 15 urban secondary schools in Sandakan, Sabah with a population of 112 English teachers. The approaches and activities conducted in the literature lesson were identified whilst the reasons to why teachers employed the approaches and activities were explicated. Triangulation involving the questionnaire as the primary data, classroom observation and focused interview as the secondary data was used. A total of 87 teachers responded to the questionnaire; whereas, in a related case study, an English option teacher (a TESL graduate) and a non-option teacher (a History graduate) were observed for four weeks and then be interviewed. Findings show that the paraphrastic approach (mean = 4.05) is popularly used by teachers, followed by the information-based approach (mean = 4.04) and the moralphilosophical approach (mean = 3.93). This seems to go concurrently with the findings of the case study whereby both teachers exhibited similar teaching approaches. The findings draw attention to the fact that teaching approaches are largely influenced by students' language proficiency, attitudes, the exam-oriented culture, the prescribed literary materials and the number of students in the classroom. The implication is that literature teaching which aims at generating students' personal response and appreciation maybe a futile exercise if the issues are not tackled wisely